The Role of Body Positivity in Mental Health and Self-Acceptance: A Qur’anic Perspective - Basid, Abd.; Maghfiroh, Nazilatul (TAFSE: Journal of Qur'anic Studies, 2025)
Low self-acceptance can have a significant negative impact on an individual's body image and mental health. The body positivity movement has emerged in response to unrealistic physical standards, promoting an attitude of gratitude and acceptance toward one's own body. This study examines the role of body positivity in mental health and self-acceptance from a Qur’anic perspective. Employing a qualitative, library-based research design with a thematic (maudhu'i) approach, the study analyzes relevant Qur’anic verses—namely, QS. Al-Tin: 4, QS. Al-A'raf: 31, QS. Ibrahim: 7, and QS. Al-Hujurat: 13. Data were collected from both primary and secondary sources, including classical and contemporary tafsir literature as well as relevant scientific studies. The findings demonstrate that the Qur’an embodies values supportive of body positivity, such as recognition of the perfection of human creation, the centrality of gratitude, and an emphasis on piety over physical appearance. These results indicate that the principles of body positivity are consonant with Islamic teachings and can contribute to improved mental health, self-confidence, and the reduction of stress associated with unrealistic body standards. The practical implication is that Qur’anic values may serve as a foundation for nurturing positive self-awareness and psychological well-being.